The impact of weather variation on the body condition of cape cobras (Naja nivea) in the Kalahari — implications for climate change - Kim J. Scholtz; Graham J. Alexander; Thilo F. Beck; Robin A. Maritz; Bryan Maritz (Journal of Arid Environments, 2025)

Stable climate corridors promote gene flow in the Cape sand snake species complex (Psammophiidae) - Jody M. Taft; Bryan Maritz; Krystal A. Tolley (Zoologica Scripta, 2022)
Climate shifts during the Quaternary Period have driven changes in regional range dynamics for many species, influencing population structure of species and in some cases promoting speciation. Within southern Africa, the psammophine snakes Psammophis trinasalis and P. namibensis were historically considered subspecies of P. leightoni but were elevated to species rank based on ecological differences. Preliminary phylogenetic analyses suggested intraspecific, not interspecific genetic variation between these taxa, but this finding was based on very limited data and could not be confirmed. To assess the level of genetic differentiation within the P . leightoni species complex, we explored the evolutionary history of these snakes by combining phylogenetic analyses, species distribution modelling and an examination of morphology. We generated a comprehensive, multi‐gene phylogeny for Psammophis that included wider geographic sampling of the three species in the complex. Using this phylogeny, Bayesian and distance‐based species delimitation analyses showed intraspecific, not interspecific divergences between taxa in the complex, suggesting that they collectively represent a single taxon. Furthermore, non‐metric multidimensional scaling analysis of scalation characters showed no differences between the species. Moreover, palaeo‐modelling at three time periods since the last interglacial period suggest that there have been varying levels of connectivity between these taxa, which has likely facilitated gene flow between them. Given the evidence, we propose that the P. leightoni complex represents a single species and therefore formally synonymise the three species.

The underappreciated extent of cannibalism and ophiophagy in African cobras - Bryan Maritz; Graham J. Alexander; Robin A. Maritz (Ecology, 2019)